2013
DOI: 10.1017/s0033291713001748
|View full text |Cite
|
Sign up to set email alerts
|

Sleep enhances exposure therapy

Abstract: Background: Sleep benefits memory consolidation. Here, we tested the beneficial effect of sleep on memory consolidation following exposure psychotherapy of phobic anxiety. Method: A total of 40 individuals afflicted with spider phobia according to DSM-IV underwent a one-session virtual reality exposure treatment and either slept for 90 min or stayed awake afterwards. Results: Sleep following exposure therapy compared with wakefulness led to better reductions in self-reported fear (p = 0.045, d = 0.47) and cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
68
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 51 publications
(67 reference statements)
7
68
0
2
Order By: Relevance
“…Exposure therapy provides learning situations where new therapeutic extinction memory traces are formed that then need to be consolidated and integrated with pre-existing memories and experiences (Kleim et al, 2014 shown. However, in the wake group, responses to the new spider were actually stronger than to the original spider video in Session 1 when it was first shown (sensitization).…”
Section: Effects Of Sleep After Different Types Of Exposure Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure therapy provides learning situations where new therapeutic extinction memory traces are formed that then need to be consolidated and integrated with pre-existing memories and experiences (Kleim et al, 2014 shown. However, in the wake group, responses to the new spider were actually stronger than to the original spider video in Session 1 when it was first shown (sensitization).…”
Section: Effects Of Sleep After Different Types Of Exposure Therapymentioning
confidence: 99%
“…Another study of sleep following exposure therapy for spider phobia suggested that sleep improved therapeutic effectiveness (Kleim et al, 2014). This study tested the effectiveness of sleep following virtual reality exposure therapy on extinction memory consolidation.…”
Section: Effects Of Sleep After Different Types Of Exposure Therapymentioning
confidence: 99%
“…In the recent study of Kleim et al (2014), going to sleep immediately after exposure increased the efficacy of the treatment of spider phobia, compared to staying awake after a session. The authors explain this effect by the benefits of sleep on memory consolidation found in earlier studies.…”
mentioning
confidence: 99%
“…Therefore, if exposure is followed by sleep, the spider non-fearful memories will be better reactivated when competing with spider fearful memories. Kleim et al (2014) used a 90 min-long documentary about European cities for the awake condition. We can assume that this documentary contains some cues associated with spiders, as spiders can be found in most modern homes.…”
mentioning
confidence: 99%
See 1 more Smart Citation